The Prognostic Value for Tissue Inhibitor of Metalloproteinase-2 and Fatty Acid-Binding Protein-1 as Biomarkers for Chronic Kidney Disease - Talab, Fatima Gh.; Ahmed, Hind S. (Iraqi Journal of Science, 2025)
Globally, chronic kidney disease (CKD) has emerged as a significant public health concern, characterized by high rates of morbidity and mortality. To assess the risk of kidney damage, researchers have identified tissue inhibitor of matrix metalloproteinase-2 (TIMP-2) and fatty acid-binding protein-1 (FABP-1) as valuable biomarkers. This study aims to analyse the effectiveness of specific biomarkers in assessing CKD and its associated mechanisms in Iraqi patients. The study was conducted from December 2023 to May 2024. Ninety subjects, aged 48–65 years; including 60 patients with CKD (38 male and 22 female) attended the Baghdad Teaching Hospital/ Medical City/ Dialysis Unit- Baghdad, Iraq. In addition, 30 healthy people (15 male and 15 female) were selected as a control group. The findings reveal a significant (p= 0.001) in serum TIMP-2 and FABP-1 levels among CKD patients as compared to the control group (6.30±2.19 vs. 0.62±0.21) ng/mL and (9.38±3.14 vs. 1.80±0.01) ng/mL respectively. In addition, the present results revealed a significant positive correlation (p < 0.05) between serum TIMP-2 and FABP-1 and levels of various parameters, including fasting glucose, lipid profile, and renal function tests. Conversely, a significant negative correlation (p < 0.05) was observed between serum TIMP-2 and FABP-1 levels with serum total protein, albumin, and estimated glomerular filtration rate in the CKD group. In conclusion, the study concludes that elevated serum levels of TIMP-2 and FAB-1 in CKD patients underscore their critical role in renal dysfunction. Therefore, these factors may serve as biomarkers of kidney injury progression among patients with CKD.